Rethinking modernity and national identity in Turkey - Bozdoğan, Sibel; Kasaba, Reşat, 1954- (Seattle : University of Washington Press, 1997)
The essays in this book are the first attempt to examine the Turkish experiment with modernity from a broad, interdisciplinary perspective, encompassing the fields of history, the social sciences, the humanities, architecture, and urban planning. The contributors offer a fresh, balanced understanding of dilemmas now facing not only Turkey but also many other parts of the Middle East and the world at large.
Introduction / Sibel Bozdogan and Resat Kasaba -- Kemalist certainties and modern ambiguities / Resat Kasaba -- Whither the project of modernity? Turkey in the 1990s / Caglar Keyder -- Modernization policies and Islamist politics in Turkey / Haldun Gulalp -- Projects as methodology : some thoughts on modern Turkish social science / Serif Mardin -- The quest for the Islamic self within the context of modernity / Nilufer Gole -- The project of modernity and women in Turkey / Yesim Arat -- Gendering the modern : on missing dimensions in the study of Turkish modernity / Deniz Kandiyoti -- The predicament of modernism in Turkish architectural culture : an overview / Sibel Bozdogan -- Once there was, once there wasn't : national monuments and interpersonal exchange / Michael E. Meeker -- Silent interruptions : urban encounters with rural Turkey / Gulsum Baydar Nalbantoglu -- Arabesk culture : a case of modernization and popular identity / Meral Ozbek --The Turkish option in comparative perspective / Ernest Gellner -- Modernizing projects in Middle Eastern perspective / Roger Owen -- Finding the meeting ground of fact and fiction : some reflections on Turkish modernization / Joel S. Migdal.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Turkey -- Civilization -- 20th century; Social change -- Turkey; Nationalism -- Turkey; East and West; HISTORY / Middle East / General; Civilization; East and West; Nationalism; Social change; Turkey; Moderniteit; Nationale identiteit; Sociale verandering; Cultuurverandering; Turkije; 1900-1999